Renal mucormycosis following transurethral resection of prostate in the time of COVID-19: Unique imaging features resembling emphysematous pyelonephritis - Abbas Basiri; Nastaran Mahmoudnejad; Mahmoud Parvin; Erfan Amini (Urology Case Reports, 2022)
We report a case of isolated renal mucormycosis 2 weeks following transurethral resection of prostate. The patient also mentioned history of admission for COVID-19, two months earlier. Symptoms progressed and patient underwent urgent nephrectomy. CT scan resembled imaging features of emphysematous pyelonephritis and therefore, patient did not receive timely treatment with amphotericin B in addition to nephrectomy and succumbed to the disease.